KEMULURAN DAN KEKUATAN PUTUS TALI SABUT KELAPA BERLAPIS KITOSAN: Elongation and Breaking Strength of The Chitosan-Coated Coir Rope - Didin Komarudin; Diniah Diniah; M. Dahri Iskandar; Dwi Putra Yuwandana; Yopi Novita (Bogor Agricultural University, 2020)
Coating of coconut coir rope as a material for fishing gear is carried out to inhibit the decomposition process and increase the breaking strength and elongation of the rope. In this study,the coating of coconut coir rope using chitosan as an antimicrobial is expected to inhibit the growth of micro-organisms. This study aims to determine the elongation and breaking strength of chitosancoated coconut coir ropes. The research method used is experimental. Data analysis used the Kolmogorov–Smirnov normality test and RAL (Completely Randomized Design)- to determine the effect of chitosan coating on the elongation and breaking strength of coconut fiber ropes. The results showed that the chitosan coir rope had a dark brown color, while the control coir rope had a light brown color. The direction of the twist is